Socialization of the Dangers of Drugs and Drug Crime Patterns to High School Students as an Effort to Make Teenagers Clean from Drugs in Pelalawan Regency - Zulherawan, Muhammad; Afrianda, Rendi Tri; Tutrianto, Rio; Joesyiana, Kiki (Doctoral Program of Social Science, Pasundan University, 2023)
The use of narcotics and illegal drugs (narcotics) among teenagers is considered to be caused by several things, including because Indonesia is located between three continents and considering the development of science and technology, the influence of globalization, very advanced transportation flows and rapid technological developments. very sophisticated as a target dynamic for illicit drug trafficking. Drug abuse and illicit trafficking is an increasingly widespread, complex and complicated problem faced by the Indonesian people recently, because it can cause various negative impacts, especially among the younger generation, such as health problems, social and economic problems, and also politics. Drugs have a very broad negative impact both physically, psychologically, economically, socially, culturally, on defense and security, and others. Those who use drugs will feel dependent after continuous use. The drug problem in Indonesia is still something that is urgent and complex. In the last decade this problem has become widespread. This is proven by the significant increase in the number of drug abusers or addicts, along with the increasing disclosure of drug crime cases with increasingly diverse patterns and increasingly massive syndicate networks. The impact of drug abuse not only threatens the survival and future of the abuser, but also the future of the nation and state, regardless of social, economic strata, age or level of education. Various efforts to overcome the growth of drug addicts have been made, but have been hampered by weak laws.